Growth response and production of cucumber plants (Cucumis sativus L.) due to the application of cow manure and SP-36 fertilizer - Faris Yanto Laia; Harahap, Rahmaniah; Dewi, Dora Silvia (Central Research Institute For Agriculture, 2024)
Cucumber (Cucumis sativus L.) is a horticultural plant from the gourd family that is widely known in various countries. This research will be carried out in the practicum area of the Faculty of Agriculture, Indonesian Community Development University (UPMI), Medan. Jalan Wakaf, Pasar 12, Marendal, Patumbak Kampung, Deli Serdang, with an altitude of ±40 m above sea level. It will be carried out from June to August 2023. This research design uses a randomized group design (RAK) with two factor treatments, namely: Factor I: Giving Cow Manure (P), consisting of 3 levels of treatment, namely: P0: without giving fertilizer cow pen; P1: dose of cow manure 10 tons/ha equivalent to 1 kg/plot; and P2: dose of cow manure 20 tons/ha equivalent to 2 kg/plot. Factor II: Application of SP-36 (S) fertilizer consists of 3 treatment levels, namely: S0: without SP-36 fertilizer (S0), S1: SP-36 fertilizer concentration 10 grams per plot, and S2: SP-36 fertilizer concentration 20 grams per plot. Based on the research conducted, it can be concluded that the single effect of giving cow manure on the number of leaves of cucumber plants is significantly different at the ages of 6 WAP and 8 WAP but is not significantly different at the ages of 1 WAP and 4 WAP, plant height, and plant fruit production. samples and root volume. The single effect of giving SP-36 fertilizer was not significantly different on plant height, number of leaves, fruit production of the sample plants, and root volume. The interaction effect of giving cow manure and SP-36 fertilizer was significantly different on the number of leaves at the age of 6 WAP but was not different. real at the ages of 2 WAP, 4 WAP, and 8 WAP, plant height, fruit production of sample plants, and root length.